COVID-19 vaccination dynamics in the US: coverage velocity and carrying capacity based on socio-demographic vulnerability indices in California's pediatric population - Alexander A. Bruckhaus; Azrin Khan; Trevor A. Pickering; Aidin Abedi; Aidin Abedi; Aidin Abedi; Sana Salehi; Dominique Duncan (Frontiers Media S.A., 2023)
IntroductionCOVID-19 vaccine inequities have been widespread across California, the United States, and globally. As COVID-19 vaccine inequities have not been fully understood in the youth population, it is vital to determine possible factors that drive inequities to enable actionable change that promotes vaccine equity among vulnerable minor populations.MethodsThe present study used the social vulnerability index (SVI) and daily vaccination numbers within the age groups of 12-17, 5-11, and under 5 years old across all 58 California counties to model the growth velocity and the anticipated maximum proportion of population vaccinated.ResultsOverall, highly vulnerable counties, when compared to low and moderately vulnerable counties, experienced a lower vaccination rate in the 12-17 and 5-11 year-old age groups. For age groups 5-11 and under 5 years old, highly vulnerable counties are expected to achieve a lower overall total proportion of residents vaccinated. In highly vulnerable counties in terms of socioeconomic status and household composition and disability, the 12-17 and 5-11 year-old age groups experienced lower vaccination rates. Additionally, in the 12-17 age group, high vulnerability counties are expected to achieve a higher proportion of residents vaccinated compared to less vulnerable counterparts.DiscussionThese findings elucidate shortcomings in vaccine uptake in certain pediatric populations across California and may help guide health policies and future allocation of vaccines, with special emphasis placed on vulnerable populations, especially with respect to socioeconomic status and household composition and disability.